ASSOCIATION OF WEIGHT CHANGE IN BREAST CANCER PATIENTS UNDERGOING TAMOXIFEN TREATMENT AT A TERTIARY CARE CENTRE, SINDH, PAKISTAN - Shahid, Aisha; Haider, Ghulam; Khan, Mehwish Roshan; Nouman, Maryum; Pavan, Bhunisha; Rahool, Raja; Mehar, Khalil; Zahoor, Saima; Ahmed, Moiz; Abbas, Kiran (Journal of Ayub Medical College Abbottabad, 2021)
Background: Tamoxifen is a selective oestrogen receptor modulator; in the breast, it decreases the growth and proliferation of breast epithelial cells. We assessed the weight change after Tamoxifen use in breast cancer patients. Methods: This was a single-centred, prospective, observational cohort study. All patients diagnosed with breast cancer with ER and/or PR positivity were enrolled in the study. Out of these, 90 patients who have been prescribed Tamoxifen treatment either in adjuvant or palliative setting gave their consent to participate. Demographic data, treatment plan, menstrual status, weight, BMI, serum fasting lipid profile, change in diet, and change in physical activity were recorded at the time of diagnosis and then quarterly until 1 year of treatment. Results: A mean age of 42.12±8.5 years was reported, and the mean weight was 62.22±10.6 kg. The majority of the patients, i.e., 68 (75.55%) had advanced tumour stages (III and IV). The study reported that the mean weight of the patients changed significantly at different time intervals during the treatment course (p<0.0005). Moreover, there was an upward trend in weight from the time of starting Tamoxifen to 3-months (62.22±1.51 kg vs 62.88±1.45 kg, respectively). There was a statistically significant increase in weight at 6-month, 9-month, and 12-month of Tamoxifen treatment (63.72±1.46 kg, 64.35±1.42 kg, 65.12±1.44 kg, respectively). Also, most of the patients gained weight as time passed by. Conclusion: This study indicated that Tamoxifen has a significant correlation with the increase in weight in hormone receptor-positive breast cancer patients in our population